Liberia : Staff Report for the 2006 Article IV Consultation and Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
Liberia's 2006 Article IV Consultation reports that the economy continues its modest recovery, driven by donor-related expenditure and the resumption of activity in rural areas. The government has endorsed the Governance and Economic Management Assistance Program that aims to strengthen economic governance and financial management and rebuild Liberia's key economic institutions. Reestablishment of confidence in these institutions is crucial to maintaining stability, securing sustained external support, and encouraging private investment.